2022
DOI: 10.2147/idr.s366308
|View full text |Cite
|
Sign up to set email alerts
|

Serum Interleukin-26 is a Potential Biomarker for the Differential Diagnosis of Neurosyphilis and Syphilis at Other Stages

Abstract: Background Interleukin-26 (IL-26) is an atypical proinflammatory cytokine due to its binding to circulating double-stranded DNA and direct antibacterial activity. Although IL-26 has been confirmed to be involved in the pathophysiology of cancer, chronic inflammatory diseases and infections, the diagnostic and prognostic values of IL-26 levels in syphilis patients are not clear. This study aimed to investigate IL-26 levels in different stages of syphilis progression. Methods … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 27 publications
0
4
0
Order By: Relevance
“…Xie et al reported that serum ubiquitin C-terminal hydrolase-L1 (UCH-L1), glial fibrillary acidic protein (GFAP) and neurofilament light protein (NF-L) had pleasant performances in the diagnosis of NS [ 26 , 27 ]. Shen et al found that circulating IL-26 in serum displayed diagnostic potential in the progression of NS [ 28 ]. Chen et al analyzed the exosomal miRNA profiles in the serum of syphilis patients, and found NS patients showed a significant upregulation in miR-590-5p, miR-570-3p and miR-570-5p [ 29 ].…”
Section: Discussionmentioning
confidence: 99%
“…Xie et al reported that serum ubiquitin C-terminal hydrolase-L1 (UCH-L1), glial fibrillary acidic protein (GFAP) and neurofilament light protein (NF-L) had pleasant performances in the diagnosis of NS [ 26 , 27 ]. Shen et al found that circulating IL-26 in serum displayed diagnostic potential in the progression of NS [ 28 ]. Chen et al analyzed the exosomal miRNA profiles in the serum of syphilis patients, and found NS patients showed a significant upregulation in miR-590-5p, miR-570-3p and miR-570-5p [ 29 ].…”
Section: Discussionmentioning
confidence: 99%
“…Increased concentrations of the chemokines CXCL13, CXCL8, and CXCL10 in the CSF or their CSF/serum ratio, particularly in the case of CXCL13, can predict the occurrence of neurosyphilis (45). In addition, levels of macrophage migration inhibition factor in the CSF, peripheral blood CD8+IFN-γ+ cells, levels of serum IL-26, and antibody index (AI) for intrathecal synthesis of specific anti-treponemal IgG were predictive of neurosyphilis (46)(47)(48)(49). Furthermore, abnormal expression of mir-590-5p, mir-570-3p, mir-570-5p, and mir-21-5p in serum and CSF is another potential biomarker of neurosyphilis (50).…”
Section: New Diagnostic Indicators and Strategies (N)mentioning
confidence: 99%
“…Elevated concentrations of CXCL8, CXCL10, and IL-10 may also be potential biological markers of neurosyphilis, especially asymptomatic neurosyphilis [ 37 39 ]. Meanwhile, the increased levels of CXCL9, CXCL7, CCL24, IL-17, IL-26, and migration inhibitory factor (MIF) of macrophages in the CSF of neurosyphilis patients suggested their role as promising differential diagnostic tools for neurosyphilis [ 37 , 40 42 ]. Although these cytokine changes are still in their infancy for the diagnosis of neurosyphilis, their importance cannot be ignored due to the lack of ideal neurosyphilis biomarkers.…”
Section: Diagnosismentioning
confidence: 99%